Maybe baby: uncertainty and decision in Sheila Heti's Motherhood. Issue 1 (2nd January 2022) - Currie, Mark
ABSTRACT: Sheila Heti's Motherhood represents the struggle to make a decision under conditions of uncertainty. This essay examines the category of writing as it figures in that struggle, as a factor in the decision, as a metaphor for necessity, and as an aleatory compositional practice. It explores the logic of the 'decision not to' and argues that the resemblance between deciding not to do something and not deciding anything at all is understood, in this work, through a form of resemblance between the temporal positions of the 'not yet' and the 'always already'. I argue here that these time-bound conceptualisations of decision making are at the centre of Motherhood 's enquiry into contingency and necessity, which is conducted in open discussion of biblical stories, but also through a less visible relation with Herman Melville's Bartleby . Heti's discussion of the decision, and the idea of a decision, develops reflections on writing, potentiality and embodiment that are missing in the philosophical reception of Bartleby, and make a significant addition to recent writings on the topic of contingency.